Software Quality Assurance Models and Application to Defect Prediction Techniques - Mona, Jammel; Abdulzhraa Al-Sagheer, Radhwan Hussein; Alghazali, Salah.M.M. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The needs for hardware and software applications have emerged because of recent technological breakthroughs. Along with this advancement in technology, the need for software across a wide range of applications has dramatically increased. Any software sector, creating high-quality software and preserving its renown for users the most crucial undertaking for the expansion of the software industry. This must be accomplished, for software industries, software engineering is crucial. However, applying such standards to instill trust in the minds of consumers is not always straightforward. In general, the software development team perceives quality assurance in software development as an additional lengthy and extremely documentation-intensive operation that is of little value to the client. Consequently, this paper will demonstrate that the quality of the notion can be addressed from various perspectives depending on the individual’s take and interest might be challenging to determine. In addition, we discussed some standards, models and applications of quality and assurance in software engineering by utilizing soft computing-based machine learning approaches that help to forecast, optimize, and efficiently learn the features, we intend to develop an effective method for predicting software defects.